The Effect Of Liquidity, Profitability And Leverage Ratios On Stock Prices In Food And Beverage Companies Listed On The Indonesia Stock Exchange For The 2017-2021 Period - Muhammad Ivan Syahbana; Putri Zanufa Sari (NAROTAMA UNIVERSITY, Indonesia, 2023)
This research aims to analyze and determine the influence of L ikuiditas, Profitability and Leverage on Harga Saham partially and simultaneously on food and beverage sub-sector companies listed on the Indonesia Stock Exchange peroide 2017-2021. This type of research uses qualitative research. The determination of samples in this study used purposive sampling which contained 95 samples. Multiple Linear Regression is the analytical method used in this study. The results showed that in this research, partially the ratio of Liquidity, Profitability and Leverage affects the stock price. Simultaneously the ratio of Liquidity, Profitability, and Leverage affects the stock price.